Recent Advances in the Synthesis of the Antidepressant Paroxetine - Santos, Joana; Proença, Maria F.; Rodrigues, Ana Joao; Patrício, Patricia; Domingues, Helena Sofia (Current Medicinal Chemistry, 2021)
Paroxetine is a potent inhibitor of serotonin reuptake and is widely prescribed for the treatment of depression and other neurological disorders. The synthesis of paroxetine and the possibility to prepare derivatives with a specific substitution pattern that may allow their use as biological probes is an attractive topic especially for medicinal chemists engaged in neurosciences research. Considering the extensive work that was developed in the last decade on the total synthesis of paroxetine, this review summarizes the most important contributions in this field, organized according to the reagent that was used as a starting material. Most of the methods allowed to prepare paroxetine in 4-9 steps with an overall yield of 9-66%. Despite the progress made in this area, there is still room for improvement, searching for new eco-friendly and sustainable synthetic alternatives.
Keywords: 3-dicarbonyl compounds